2013
DOI: 10.1371/journal.pcbi.1003171
|View full text |Cite|
|
Sign up to set email alerts
|

Task-Based Core-Periphery Organization of Human Brain Dynamics

Abstract: As a person learns a new skill, distinct synapses, brain regions, and circuits are engaged and change over time. In this paper, we develop methods to examine patterns of correlated activity across a large set of brain regions. Our goal is to identify properties that enable robust learning of a motor skill. We measure brain activity during motor sequencing and characterize network properties based on coherent activity between brain regions. Using recently developed algorithms to detect time-evolving communities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
462
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 350 publications
(496 citation statements)
references
References 97 publications
(161 reference statements)
33
462
1
Order By: Relevance
“…1. Furthermore, recent evidence indicates a core common network exists in human and macaque brains and that it is tightly connected [2]. In this work we develop, for the first time, a group-wise core SCN extraction algorithm which guarantees a connected network output.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1. Furthermore, recent evidence indicates a core common network exists in human and macaque brains and that it is tightly connected [2]. In this work we develop, for the first time, a group-wise core SCN extraction algorithm which guarantees a connected network output.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting graph can be a set of disconnected subgraphs. This is problematic, recent studies have shown the core network to be tightly connected [2]. However, extracting connected group-wise core SCN is far from simple: an algorithm to find the largest core network of a population cannot find an approximated solution in polynomial time.…”
Section: Discussionmentioning
confidence: 99%
“…First, data analysis approaches that move beyond traditional mean activation estimates will offer new perspectives on social influence, for instance, by examining neural networks rather than individual regions [51,52]. Specific examples of this would include using techniques derived from graph theory [53][54][55][56], connectivity analysis [57], or cognitive architectures [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…There has been burgeoning evidence on the dynamism of network modules that have been shown to continually evolve and reconfigure across time and cognitive states [20]. fMRI studies have also shown existence of less modular configurations in the brain during resting state where there is a cross-talk between different modules [21].…”
Section: Dynamics Of the Realms Governs Ensuing Behaviourmentioning
confidence: 99%